Hubungan antara Tingkat Partisipasi Ibu dalam Kegiatan Posyandu dengan Pengetahuan Gizi Ibu dan Status Gizi Balita: Relation of Mothers’ Participation Level in Posyandu to Mothers’ Nutritional Knowledge and Nutritional Status of Children Under Five - Siti Aisyah Solechah; Norhasanah; Suryani, Nany; Fathullah, Desya Medinasari; Nisa, Ainun; Hekmah, Nurul; Yudistira, Sigit (UNIVERSITAS NGUDI WALUYO, 2024)
People’s low participation level in Posyandu activities still becomes one of the problems at Puskesmas in Banjarbaru. It can be observed from the D/S achievements that were still lower than the target set by the Puskesmas. D/S achievement at the Puskesmas Landasan Ulin (58.4%) in 2021 was still far from the target (90%). This study aimed to analyze the relation of mothers’ participation level in Posyandu activities to mothers’ nutritional knowledge and nutritional status of children under five. This observational study used a cross-sectional design involving 95 pairs of children under five and their mothers selected by the purposive sampling technique. This study was conducted from November to December 2022. The mothers’ participation level in Posyandu activities was assessed using questionnaires and the nutritional status of under-fives was determined using anthropometric measurements. The data were analyzed using the Spearman Rank test. The results showed that mothers’ participation level in Posyandu activities was associated with mothers’ nutritional knowledge (p=0.022; r=-0.234) but not associated to the nutritional status of children under five based on the WAZ index (p=0.888). ABSTRAK Tingkat partisipasi masyarakat dalam kegiatan Posyandu yang rendah masih menjadi salah satu masalah gizi di Puskesmas-Puskesmas Kota Banjarbaru. Hal ini dapat dilihat dari capaian D/S yang masih kurang dari target yang ditentukan oleh Puskesmas. Capaian D/S di Puskesmas Landasan Ulin (58,4%) pada tahun 2021 masih jauh dari target yang ditetapkan oleh Puskesmas tersebut (90%). Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat partisipasi ibu dalam kegiatan Posyandu dengan pengetahuan gizi ibu dan status gizi balita. Penelitian observasional ini menggunakan desain cross-sectional yang melibatkan 95 pasang balita dengan ibunya yang diambil dengan teknik purposive sampling. Penelitian ini dilakukan dari bulan Oktober hingga Desember 2022. Tingkat partipasi ibu dalam kegiatan Posyandu diperoleh menggunakan kuesioner dan status gizi balita ditentukan melalui pengukuran antropometri. Data dianalisis menggunakan uji Spearman Rank. Tingkat partisipasi ibu dalam kegiatan Posyandu berhubungan signifikan (p=0,022; r=-0,234) dengan pengetahuan gizi ibu tetapi tidak berhubungan dengan status gizi balita berdasarkan indeks BB/U (p=0,888).